The works of William Harvey - Harvey, William, 1578-1657 (Classics in medicine and biology series., 1989)
William Harvey's revolutionary book on the circulatory system, published in Latin in 1628, demonstrated for the first time how the heart pumps blood through the body. His findings overturned the world's basic understanding of the way the body functions and changed fundamental knowledge of physiology as much as any scientific work in history. The Works of William Harvey will provide scientists, students, physicians, and interested lay persons access to the original works of a pioneer who shaped contemporary science. This edition is a reissue of the 1965 facsimile of the 1867 collection and translation of Harvey's works. Included are his groundbreaking 1628 book on the circulatory system, a book on animal reproduction, and various shorter scientific writings and letters, along with a new introduction.